KORELASI ASPEK DEMOGRAFI TERHADAP KEPATUHAN PASIEN DIABETES MELLITUS DALAM PEMBERIAN INSULIN SECARA MANDIRI - Yoyoh, Imas; Aryatika, Karera; Saputra, M. Khalid Fredy; Bernadetha, Bernadetha (Ensiklopedia of Journal, 2025)
Abstract: Diabetes Mellitus (DM) is one type of chronic disease that is long-term and requires ongoing treatment. Non-adherence to treatment in patients with Diabetes Mellitus (DM) is still a serious challenge in efforts to manage this disease effectively. The purpose of the study was to determine the correlation of demographic aspects with compliance of diabetes mellitus patients in self-administration of insulin. The research design used in this study was cross sectional. The research was conducted at Siaga Medika General Hospital. The research was conducted in July 2024. The population is all patients who have diabetes mellitus. The sample amounted to 75 people. The sampling technique used in this study was Simple Random Sampling. Data analysis was performed univariate and bivariate. The results showed a relationship between education (p value: 0.045) and work (p value: 0.012). It is recommended that diabetic patients can maintain, foster, and increase self-awareness to always seek information, increase compliance and enthusiasm, in undergoing diabetes mellitus treatment.Keywords: Compliance, Education, Occupation